2014
DOI: 10.1038/srep04686
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced Room Temperature Ferromagnetism in Glassy Chromites

Abstract: We report an unusual robust ferromagnetic order above room temperature upon amorphization of perovskite [YCrO3] in pulsed laser deposited thin films. This is contrary to the usual expected formation of a spin glass magnetic state in the resulting disordered structure. To understand the underlying physics of this phenomenon, we combine advanced spectroscopic techniques and first-principles calculations. We find that the observed order-disorder transformation is accompanied by an insulator-metal transition arisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Specifically, since Cr 3+ can be further oxidized to higher valence states, oxygen-rich secondary phases can emerge [10]. Moreover, the choice of substrate is important to eliminate the formation of polycrystalline films [11,12]. To date, layer-by-layer growth of high-quality epitaxial YCO films has not been demonstrated.…”
mentioning
confidence: 99%
“…Specifically, since Cr 3+ can be further oxidized to higher valence states, oxygen-rich secondary phases can emerge [10]. Moreover, the choice of substrate is important to eliminate the formation of polycrystalline films [11,12]. To date, layer-by-layer growth of high-quality epitaxial YCO films has not been demonstrated.…”
mentioning
confidence: 99%
“…In amorphous YCrO 3 thin films deposited by the pulsed laser, Araujo et al observed a FM order above room temperature [121]. The reported order-from-disorder phenomenon was accompanied by a phase transition from an insulating to a metal state, which was attributed to the wide distribution of bond angles (Cr-O-Cr) and the resultant metallization via free carriers [121]. X-ray absorption spectroscopy shows the formation of Cr 4+ oxidation state in the YCrO 3 thin film (see Fig.…”
Section: Thin Filmsmentioning
confidence: 99%
“…A hysteresis of polarization-electric (P-E) loop of the polarization curve presents at 300, 325, and 350 K [72]. Previous studies of YCrO 3 compound focused mainly on polycrystals [74,98,[100][101][102][103][104][105][106][107][108], nanocrystals [109][110][111][112][113][114][115], and thin films [72,83,86,[116][117][118][119][120][121][122][123][124][125][126][127][128][129]. The lack of high-quality and large-scale single-crystalline samples has been a long-standing issue for realizing potential applications to some extent and studying their intrinsic physical properties [130][131][132][133][134][135][136][137].…”
Section: Introductionmentioning
confidence: 99%